Program of Rehabilitation and Functional Performance of Patients with Parkinson Disease Naval Medical Center “Cirujano Mayor Santiago Távara” - Díaz-Meyzan, LesLy (2021)
Objective. To determine the existing association between the application of the Rehabilitation Program (RP) and the Functional Performance (DF) of patients with Parkinson's disease at the Naval Medical Center “Cirujano Mayor Santiago Távara”. Methods: analytical, longitudinal, retrospective cohort study, in 18 months. With a sample of 46 patients,in two cohorts, Functional Performance was determined by dimensions of basic activities (Barthel indices), strength and endurance (SPPB) and gait speed. Five values or categories were used to determine dependency, frailty, and incoordination. Normality was determined using the Kolmogorov-Smirnov test and the Mann-Whitney U was used for statistical analysis, a significant value of p <0.05 was considered. Results: The mean age of patients was 79 +/- 3 years (range: 76-82) of the exposed cohort and 72 +/- 3 years (69-75) of the cohort not exposed to RP, 33 (71,7 %) were men of the total sample. 54.3 % (25) had one or more falls and in 45.6 % (21) their caregiver was a relative. There is a direct association between PR and DF (p = 0.009) and in their dimensions: basic activities (p = 0.001), strength and endurance (p = 0.001) and gait speed (p = 0.001). The cohort or group exposed to RP improved in autonomy and independence, resistance and balance in relation to the group that did not participate in RP. Conclusions: there is a direct association between PR and DF in all its dimensions: basic activities, strength and endurance, and gait speed. The longer the PR duration, the better DF is shown.